Vibration Criteria Assessment due to Piling Works - Tuan Chik, Tuan Norhayati Binti; Cheng , Sok Rou; Kamarudin, Ahmad Fahmy; Seyed Jamalaldin, Seyed Jamalaldin; Yusoff, Nor Azizi (International Journal of Integrated Engineering, 2021)
In the recent years, the level and nature of the ground vibrations has been more concerned in worldwide. Vibration affected on surrounding building is often associated with the vibration from the ground that is mainly caused by internal and external sources. One of the external sources is construction activities. Identify the effects of vibration caused by piling works in construction sites was the purpose of this paper. It is also aiming to determine the vibration criteria due to piling works in Klang Valley construction site. In addition, the objective of this study is to compare the level of vibration with Department of Environment (DOE) guideline between both Kajang MRT and Klang Valley MRT construction sites. The data used for this study is obtained from past researchers and field testing is performed by using Polytec Laser Doppler Vibrometer and Rion VM-55. The data has been analyzed by using ModalV of MATLAB software. Based on the results, it can be concluded that the vibration amplitude for three distance includes 5m, 10m and 20m are located above the ISO level which stated that the area within the distances not suitable for placement of sensitive equipment. The highest value of root mean square velocity is occurred in the distance of 5m and the reading is 80000 Âµm/s. According to Department of Environment (DOE) guidelines, the vibration at distance of 1m and 3m at Kajang MRT will cause major damage to surrounding buildings while minor damage was produced by the vibration at 5m, 10m and 20m distance from bored piling point which located around the area of Klang Valley MRT.